DNA as an Evidence in Islamic Jurisprudence - Dr. Hafiz Mohsin Zia Qazi; Dr. Rafi Ullah; Dr. Saeed Ahmad; Dr. Rab Nawaz (Al-Qanṭara, 2022)
Abstract Islam support science, although Qurʾān is not a book of science yet 750 verses of Holy Qurʾān discussed nature and natural phenomena including the chemical and biological creation of man. The discovery of DNA has been proved as a milestone in history of science. A single strand of DNA stores complete information of a person and this information is now used in chemical investigation by forensic DNA analysis. DNA analysis helps in investigation of a huge number of crime cases. Advanced countries used this technique widely and developed DNA data base for alleviation of crime. Only single cell of a body is required to extract DNA that is needed for DNA analysis and it can be done through various techniques. DNA test is also used successfully in resolving of rape crimes. Rape is a serious social crime, because a rapist not only violates rights of Allah but also violate right of people that’s why most Muslim scholars place act of rape in hirabah and differentiate it from zina. As rape is different from zina so criteria for punishment of zina will not be the same where four witnesses are required for proof. In rape cases circumstantial evidences supposed to be the primary evidence. Holy Prophet SAW and Muslim judges used circumstantial evidences throughout the history. DNA is strong, conclusive circumstantial evidence for proof of rape sexual offence. Possibility of error is always present in every human act. Even testimony of witness is also false and may affected by dellusions and illusions. Possibilities of errors in DNA test are eliminated if proper procedures are developed for detection, collection and preservation of samples. Justice is the main virtue of Islam. Allah Almighty proposed rule in Holy Qurʾān and Sunnah to provide justice equally to all. This study suggest that DNA test helps the Muslim judges to provide justice and alleviate rape crime from society.